Student’s perception on learning english online during the ‘Study From Home' (SFH) - Hidantikarnillah, Vicky; Adiyan, Fidiatun; Nurjanah, Annisa Fitri (Universitas Tangerang Raya, 2024)
This paper will explain students' perceptions regarding distance learning (online). In the current era, to be precise starting March 2020 the Corona virus pandemic (Covid-19) continues to spread so that all activities outside the home must be limited, especially school activities. The government decided to hold online activity such as study from home/ learning online. Learning online may be a new thing for students, therefore this study aims to find out how students perceive English learning as online during the COVID-19 pandemic. This study uses qualitative and quantitative research methods. The research objects were 40 students from MTs N 6 Bantul consisting of grades 7,8 and 9. The 40 students had to fill in all the questionnaires given. After 40 students have filled in the questionnaire, then the researcher chooses the best 5 students to fill out the questionnaire to be interviewed. The results showed that the students were happy and they really accepted the presence of online English learning. This is evidenced by the number of students who choose to agree. As many as 86% of 40 students strongly agree with this program.